Preparation of Carbon Nanoparticles from Candle and Their Characterization by Advanced Spectroscopic Methods (Dhaka University Journal of Science, 2022)
This study presents the preparation of carbon nanoparticles (CNp) from incomplete combustion of the candle under a controlled air supply. The shape, size, and purity of the prepared carbon particles were investigated by using a scanning electron microscope (SEM), energy dispersive x-ray (EDX), X-ray diffractometer (XRD), Fourier transformed infrared spectroscopy (FTIR), and laser-induced breakdown spectroscopy (LIBS). Non-uniformed size of carbon particles was observed by SEM studies. Most of the particles are spherical and the diameter is in the range between 10 and 70 nm. The formation of carbon particles was affirmed by EDX analysis. Mostly amorphous carbon material, in addition to some hexagonal crystal lattice of graphite, was identified by XRD analysis. FTIR spectroscopic analysis indicated the possible presence of oxygen with carbon in the prepared nanoparticles. LIBS analysis confirmed the existence of trace amount (< 0.01 wt%) of oxygen as an impurity with carbon in the prepared nanoparticles.Dhaka Univ. J. Sci. 69(3): 212-217, 2022 (June)